BERSEKSPRESI SENI LUKIS SEBAGAI SARANA SELF HEALING DI PANTI ASUHAN ASLAFUNA SHOLIHIN DI SEMARANG - Muhammad Akbar Farizky; Eko Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of painting as a means of self-healing for children at the Aslafuna Sholihin Orphanage in Semarang. The background of this study stems from the psychological condition of the children at the orphanage who are vulnerable to emotional stress, loss of family figures, and limited affection. Through painting, children can express emotions without verbal limitations, so this activity is considered effective as a nonverbal therapy medium that fosters emotional and spiritual balance. The study used a mixed methods approach with an embedded design, which combines quantitative data in the form of children's anxiety and spirituality scales, as well as qualitative data through interviews, observations, and analysis of artworks. The test results showed a decrease in children's anxiety before and after painting with an overall average ranging from 3% to 34%, with an average general decrease of around 19–20%. Analysis of the artworks showed that painting activities helped children channel negative emotions, foster a sense of security, and strengthen spiritual values through symbols and colors. The themes of the paintings that emerged, such as